The chain mediating role of C-reactive protein and triglyceride-glucose index between lung function and cognitive function in a systemic low-grade inflammation state. (November 2022) - Chen, Chen; Lu, Zhonghai; Wang, Xueyan; Zhang, Jiesong; Zhang, Dongfeng; Li, Suyun
Abstract: Objectives: This study examined whether serum C-reactive protein (CRP) level and triglyceride-glucose index (TyG) explained the association between lung function and subsequent cognitive function in middle-aged and older adults with a systemic low-grade inflammation state. Design: A prospective cohort study. Setting and participants: The sample consisted of 1, 742 participants recruited from the English Longitudinal Study of Ageing (ELSA). Methods: Lung function and covariates were measured at baseline (wave 4, 2008/09). Serum CRP level and TyG were examined at a four-year follow-up (wave 6, 2012/13). Cognitive function was assessed at eight years post baseline (wave 8, 2016/17) in the main interview. The mediation was initially assessed using multivariate linear regression models. Indirect effects were assessed using the structural equation modeling and the bootstrap method. Results: We observed that serum CRP level and TyG significantly mediated the relationships between lung function (forced expiratory volume in 1s (FEV1) and forced vital capacity (FVC)) and cognitive function (immediate recall and delay recall). Moreover, serum CRP level mediated the association between lung function (FEV1 and FVC) and TyG. Our finding also suggested that FEV1 (1.19% mediated) and FVC (1.72% mediated) might influence cognitive function partly through the chain mediating role of both serum CRP level and TyG. Conclusions and implications: The present study revealed that serum CRP level and TyG play a chain mediating role in the relationship between lung function at baseline and subsequent cognitive impairment in a nationally representative cohort of middle-aged and older adults with a systemic low-grade inflammation state.